Audit Verification Factors: The Effect of Voluntary Disclosure and Capital Market Reactions on Creative Business Companies - Effendi, Bahtiar (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2025)
This study investigates the impact of voluntary disclosure and capital market reactions on audit verification in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. Voluntary disclosure is measured using the earnings forecast horizon and forecast accuracy, while market reaction is proxied by changes in stock prices. The research employs a quantitative method with purposive sampling, resulting in a final sample of 25 companies and 75 firm-year observations. The initial population consisted of 182 manufacturing companies listed on the IDX, from which 25 companies were selected based on specific criteria. Multiple linear regression is used to test the hypotheses after classical assumption tests are conducted. The results indicate that voluntary disclosure, both in terms of forecast horizon and accuracy, does not significantly affect audit verification. Likewise, market reaction does not have a significant influence on audit verification. These findings suggest that external auditors do not heavily rely on voluntary information or market signals when conducting verification procedures. Instead, they tend to prioritize objective and mandatory disclosures to support audit evidence. This study contributes to the audit literature by providing insights into how auditors perceive and utilize non-mandatory information in emerging markets. Practically, the findings may assist auditors and regulators in evaluating the relevance of voluntary disclosures and market indicators as part of audit planning and risk assessment processes. Future research is recommended to explore additional factors that may affect audit verification, use alternative proxies for disclosure, and consider a longer observation period to obtain more robust and generalizable findings.